(untitled) (International Journal of Creative Future and Heritage (TENIAT), 2025)
ABSTRACT Pantun, a traditional Malay poetic form, is a significant element in Southeast Asian cultural heritage, known for its structured stanzas and deep symbolism. This paper examines the role of pantun in the script Si Bongkok Tanjung Puteri, focusing on how its symbolic and aesthetic elements enhance the narrative and main themes. The study uses a qualitative approach to analyse the pantun in the script, emphasising the use of metaphors and natural imagery to convey complex emotions and cultural values. The findings show how pantun illustrates themes of love, societal norms, and sacrifice, adding depth to the narrative and enriching Malay cultural expression in modern literature. ABSTRAK Pantun, sebagai bentuk puisi tradisional Melayu, adalah elemen penting dalam warisan budaya Asia Tenggara, terkenal dengan struktur stanzanya yang teratur dan simbolisme yang mendalam. Kertas kerja ini mengkaji peranan pantun dalam skrip Si Bongkok Tanjung Puteri, dengan fokus pada bagaimana elemen simbolik dan estetik pantun memperkaya naratif dan tema utama. Kajian ini menggunakan pendekatan kualitatif untuk menganalisis pantun dalam skrip tersebut, dengan menekankan penggunaan metafora dan imejan alam untuk menyampaikan emosi serta nilai budaya yang kompleks. Penemuan kajian menunjukkan pantun menggambarkan tema cinta, norma sosial, dan pengorbanan, yang memberikan maksud kepada pengisahan cerita dan memperkaya ekspresi budaya Melayu dalam kesusasteraan moden.